Association of fatigue and psychological distress with quality of life in patients with a previous venous thromboembolic event - Lukas, Paul S.; Krummenacher, René; Biasiutti, Franziska Demarmels; Begré, Stefan; Znoj, Hansjörg; von Känel, Roland (Thrombosis and Haemostasis, 2009)
Health-related quality of life (QoL) has been associated with several social and medical conditions in patients with deep vein thrombosis (DVT) and pulmonary embolism (PE).To the best of our knowledge,there is no study investigating the relationship of QoL with psychological variables in this patient population.We assumed as a hypothesis an association between heightened levels of fatigue and psychological distress, as well as decreased QoL in patients with an objectively diagnosed venous thromboembolic event. Study participants were 205 consecutively enrolled out-patients (47.4 years, 54.6% men) with DVT and/or PE. Approximately 10 days before blood collection for thrombophilia work-up, QoL, fatigue, and psychological distress were assessed using the Short Form Health Survey (SF-12), the Multidimensional Fatigue Symptom Inventory Short Form (MFSI-SF) as well as the Hospitality Anxiety and Depression scale (HADS). After controlling for demographic and medical factors, fatigue (p<0.01) but not psychological distress (p>0.05) was negatively associated with physical QoL, explaining 11.0% of the variance. Fatigue (p<0.001) and psychological distress (p<0.001) were significant predictors of mental QoL,explaining an additional 36.2% and 3.6% of the variance. Further analyses revealed that all subscales of the HADS (e.g. anxiety and depression) and of the MFSI-SF (e.g. general fatigue, physical fatigue, emotional fatigue, mental fatigue and vigor) were significant predictors of mental QoL. MFSI-SF subscales also predicted physical QoL. The findings suggest that fatigue and psychological distress substantially predict QoL in patients with a previous venous thromboembolic event above and beyond demographic factors.
Keywords: Quality of life; psychological distress; fatigue; pulmonary embolism; thrombophilia; deep venous thrombosis